The challenge of safe and sustainable development of the unmanned ship: seeking for effective legal responses - Shao, Yude; Yu, Yanan; Ma, Yanqiu (Frontiers in Marine Science, 2024)
Technological innovation is changing the way maritime transport is done, and automated driving is one of the hot topics, including unmanned ships that use automated driving technology, but legal challenges to the application of unmanned ships in the shipping industry must be resolved before that happens—whether and how the principles of existing international conventions regarding unmanned ships. To deal with this problem, it is far from enough to rely on the efforts of international organizations or the revision of international conventions. The paper analyzes several typical legal issues faced by unmanned ships: the legal definition of unmanned ships, the seaworthiness of unmanned ships, the master and crew rules, and the collision and rescue of unmanned ships, taking China as an example, the paper explains reasonable and effective legal path of domestic and international laws, trying to seek solutions at the level of domestic law beyond international convention. The paper concludes that the traditional navigation rules have largely been developed to meet the needs of manned transportation, and cannot be fully applied to unmanned ships. Therefore, until there is an international regulation specifically for unmanned ships, it would be appropriate to interpret or revise existing international conventions to apply to unmanned ships. And for countries including China, it is important to consider the improvement of domestic laws.